2011
DOI: 10.20429/ijsotl.2011.050208
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Student Thinking about Experimental Design and the Roles of Control Experiments

Abstract: Well-designed "controls" distinguish experimental from non-experimental studies. Surprisingly, we found that a high percentage of students had difficulty identifying control experiments even after completing three university-level laboratory courses. To address this issue, we designed and ran a revised cell biology lab course in which students participated in weekly "experimental control exercises." To measure student understanding of control experiments, we developed a set of assessment questions; these were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 20 publications
3
28
0
Order By: Relevance
“…At the same time, particularly for biology, the explosion of fundamental content makes it impossible for faculty to cover, let alone teach, “basic” material even to the same depth it was covered in the introductory courses of their own undergraduate years (Hoskins and Stevens, 2009). In addition, despite having encountered them in multiple courses, students may fail to retain key concepts (e.g., function of control experiments; see Shi et al ., 2011). Our compromise was to base a freshman course on particular examples of scientific literature, choosing topics in a limited range of content areas and focusing in-depth on scientific thinking and data analysis.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, particularly for biology, the explosion of fundamental content makes it impossible for faculty to cover, let alone teach, “basic” material even to the same depth it was covered in the introductory courses of their own undergraduate years (Hoskins and Stevens, 2009). In addition, despite having encountered them in multiple courses, students may fail to retain key concepts (e.g., function of control experiments; see Shi et al ., 2011). Our compromise was to base a freshman course on particular examples of scientific literature, choosing topics in a limited range of content areas and focusing in-depth on scientific thinking and data analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Students quickly identify the lack of random sampling or controls in the Wakefield study (Wakefield et al ). This is a positive outcome because previous work has shown that students struggle with designing experiments with appropriate controls (Shi et al ). In this exercise, students are also usually able to understand and explain that the lack of random sampling prevents cause and effect to be inferred from the data.…”
Section: The Problemmentioning
confidence: 99%
“…‘Experimental design’ is frequently emphasised as the most important aspect of a good study (Festing 2003), but the meaning of the phrase is not clearly articulated to students and is rarely addressed explicitly in learning activities (Chaplin ; Hiebert ). As a result, students starting an undergraduate science degree can have a very poor understanding of fundamental requirements of reliable, robust and valid experiments (Dasgupta et al ; Deane et al ; Festing ; Hiebert ; Pollack ; Shi et al ). However, in science subjects, the need for good experimental design is a threshold concept, one which learners need to master before they can make progress in their discipline (Meyer and Land ; ).…”
Section: The Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…These large-scale changes require significant investment of the instructor’s time and re-allocation of class time. Other attempts at emphasizing science process skills have focused on their integration into laboratory and research experiences, an option not available to all courses and instructors (DebBurman, 2002; Shi et al ., 2011; Brownell et al ., 2015; Woodham et al, 2016). Short of these large changes, could smaller scale incorporation of science process skills instruction prove useful to student learning?…”
Section: Introductionmentioning
confidence: 99%